2008
DOI: 10.1038/nnano.2008.329
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput solution processing of large-scale graphene

Abstract: The electronic properties of graphene, such as high charge carrier concentrations and mobilities, make it a promising candidate for next-generation nanoelectronic devices. In particular, electrons and holes can undergo ballistic transport on the sub-micrometre scale in graphene and do not suffer from the scale limitations of current MOSFET technologies. However, it is still difficult to produce single-layer samples of graphene and bulk processing has not yet been achieved, despite strenuous efforts to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

64
1,289
4
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 1,979 publications
(1,387 citation statements)
references
References 29 publications
64
1,289
4
12
Order By: Relevance
“…16), and aluminium powder 17 , have been used to reduce GO to produce RGO in the solution phase. The reduction of GO by pure hydrazine in the solution phase is particularly interesting because it can produce RGO of relative high quality with relatively small oxygen content 18 . Direct reduction of GO film has also been reported by exposure to hydrazine vapour and/or annealing at high temperature [19][20][21][22] .…”
mentioning
confidence: 99%
“…16), and aluminium powder 17 , have been used to reduce GO to produce RGO in the solution phase. The reduction of GO by pure hydrazine in the solution phase is particularly interesting because it can produce RGO of relative high quality with relatively small oxygen content 18 . Direct reduction of GO film has also been reported by exposure to hydrazine vapour and/or annealing at high temperature [19][20][21][22] .…”
mentioning
confidence: 99%
“…Graphene can be prepared by various methods such as micro-mechanical cleavage [2], chemical vapor deposition [8], thermal annealing of SiC [9] and arc discharge method [10]. In recent years chemical methods [11,12] of preparing graphene with some functional oxide groups, referred to as reduced graphene oxide (RGO), are getting attention to get high yield of single and a few layer graphene flakes which can be deposited on desirable substrates to make large area conducting coatings and to fabricate devices and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of this reduction step appears to have a large affect on the quality of the resulting graphene, and most recently, it has been shown that liquid anhydrous hydrazine is a very effective reducing agent and solvent for dispersion of large, high quality graphene flakes. 7 This has opened the door to a wide range of possible applications, one of which is for chemical sensors.…”
mentioning
confidence: 99%